Akuntabilitas Alokasi Dana Desa: Sebuah Pendekatan Struktural - Pancawati Hardiningsih; Septi Anggraeni (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
This study aims to explain the influence of leadership behaviors initiating structure and consideration of the commitments member of the Regional Leadership Nasyiatul Aisyiyah Buana Kendal. This study uses a quantitative method using data primary and secondary data obtained from the results of questionnaires. The respondents who used at least 60 people. Data collection techniques using questionnaires and documentation which the sample Buana Nasyiatul Aisyiyah regional leaders Kendal district and sampling techniques using data analysis method. The tools used in this research is multiple linear regression with IBM SPSS program 16. The results of this study indicate that the leadership behaviour of the initiating structure and consideration partially and simultaneously affect the commitment of members of the Nasyiatuls Aisyiyah Regional Leadership Kendal District, the influence of initiating structure leadership and consideration of organizational commitment by 50.6%, the rest is influenced by other variables